Need-supportiveness and athlete well-being: Coaches` competence-support at risk in the elite sport context throughout the season - Berntsen, H.; Ivarsson, A.; Kristiansen, E. (Current Issues in Sport Science, 2019)
The aim of this study was to explore how perceptions of coaches` behaviour affected athletes` wellbeing, by examining: (a) the potential change in perceptions of need-support from the coach (over an academic year), and (b) the within-person relationship between the three aspects of need-supportiveness and subjective vitality at the end of the winter sport season. Elite student athletes (N = 102, M age = 17.04) completed a questionnaire three times. Bayesian growth curve analyses showed that perceptions of relatedness and autonomy support were stable and high throughout the year. In contrast, perceptions of competence support decreased during the season. In addition, the results showed a credible positive within-person relationship between changes in all three facets of needsupportiveness from the coach and vitality measured at the end of the season, which supports SDT tenets. These findings reveal the importance of need-support for athletes` well-being, and show that competence support needs extra attention in the elite sport context where competence satisfaction is constantly challenged